Exploring the Use of Photo-Stories and Fiction Writing to Address HIV Stigma Among Health Professions Students. (January 2019) - Teti, Michelle; Schulhoff, Anastacia M.; Koegler, Erica; Saffran, Lise; Bauerband, L. A.; Shaffer, Victoria
HIV/AIDS stigma exists in healthcare and is harmful to people living with HIV (PLWH). Few anti-stigma interventions target undergraduate health professions students, although evidence supports reaching providers early in their training. We developed two different arts-based interventions based on Intergroup Contact Theory: a Photovoice intervention in which they viewed photo-stories of PLWH and a fiction writing intervention in which they developed characters with HIV. We present the results of a qualitative analysis of the post-intervention interviews, to elaborate on what and how students learned from both interventions. Via theme analysis, we identified three similar patterns among both sets of intervention participants. Interventions helped students to understand PLWH as "people first, " experience emotional responses to PLWH, and complicated their understanding of who was living with HIV. All three themes illustrate how Photovoice and fiction writing interrupted stereotypes about PLWH and humanized PLWH to health professions students.